Quran/ translated by Tarif Khalidi - "Khalidi,Tarif (tr.)" (London, 2008)
The Quraan, or literally arecitation, a is the central religious text of Islam and the holy book of the Muslim faith. Originally composed in Arabic in the seventh century, the Quraan collects the divine revelations passed down to the Prophet Muhammad by the Angel Gabriel over many years after his first vision in a cave. In 114 chapters, or "suras," the Quraan provides the rules of conduct that remain fundamental to Muslims todayamost important, the key Islamic values of prayer, fasting, pilgrimage, and absolute faith in God, with profound spiritual guidance on matters of marriage and family, crime and punishment, rituals, food, warfare, and charity.
Keywords: Quran